EFEKTIFITAS KOMBINASI PARTIAL PROGRESSIVE MUSCLE RELAXATION DAN SLOW DEEP BREATHING TERSTRUKTUR UNTUK MENURUNKAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI INSTALASI GAWAT DARURAT I.A. MOEIS SAMARINDA - Gatra Zakky Sabbily; Andri Praja Satria; Maridi M. Dirdjo; Misbah Nurjannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Hypertension is a health problem frequently encountered in emergency services and requires rapid management in addition to drug therapy. This paper aims to analyze the utilization of an innovative combination of partial progressive muscle relaxation and structured slow deep breathing to help reduce blood pressure in hypertensive patients in the Emergency Department of IA Moeis Regional General Hospital Samarinda. The method used is a descriptive case study on three adult patients with a medical diagnosis of hypertension who were selected purposively. The intervention was carried out in one session for approximately 15 minutes, then blood pressure was measured again after a break of approximately 5 minutes using a standard measuring instrument. The results showed a decrease in blood pressure in the third patient, namely 19/12, 15/10, and 15/9 millimeters of mercury in the measurements after the intervention compared to before the intervention. In conclusion, the combination of partial progressive muscle relaxation and structured slow deep breathing has the potential to be a safe, easy-to-implement, and useful non-pharmacological treatment intervention as a complement to medical therapy to help reduce blood pressure in hypertensive patients in emergency services.